Mixing in the Tyrrhenian Interior Due to Thermohaline Staircases - Durante, Sara; Oliveri, Paolo; Nair, Rajesh; Sparnocchia, Stefania (Frontiers in Marine Science, 2021)
Thermohaline staircases are a well-known peculiar feature of the Tyrrhenian Sea. Generated by extensive double diffusion processes fueled by lateral intrusions, they are considered to be the most stable of all the staircases that have been detected in the world ocean, seeing their persistence of more than 40 years in the literature. Double diffusion leads to efficient vertical mixing, potentially playing a significant role in guiding the diapycnal mixing. The present study investigates this process of mixing in the case of the Tyrrhenian staircases by calculating the heat and salt fluxes in their gradient zones (interfaces) and the resulting net fluxes in adjacent layers using hydrological profiles collected from 2003 to 2016 at a station in the heart of the basin interior. The staircases favor downward fluxes of heat and salt, and the results of the calculations show that these are greater where temperature and salinity gradients are also high. This condition is more frequently encountered at thin and sharp interfaces, which sometimes appear as substructures of the thicker interfaces of the staircases. These substructures are hot spots where vertical fluxes are further accentuated. Due to the increasing salt and heat content of the Levantine Intermediate Water (LIW) during the observation period, a rise in the values of the fluxes was noted in the portion of the water column below it down to about 1800 m. The data furthermore show that internal gravitational waves can modulate the structure of the staircases and very likely contribute to the mixing, too, but the sampling frequency of the time series is too large to permit a proper assessment of these processes. It is shown that, at least during the period of observation, the fluxes due to salt fingers do not reach the bottom layer but remain within the staircases.